(3faMI GdeLdhH ef KeGQ GdbdhH aj GdeVGa hGdefShHs - (3HYV GdCOHGAs; (3GdKYGdHj , CHh efUhQ YHO Gdedc Hf eMeO Hf ESeGYjd GdfjSCHhQj GdKYGdHj, CHh efUhQ GdKYGdHj,J (B429 (3g` s ((3QeVGf Hf ehSi GdYWjaj GdMfaj s)
(3ChdgG (B:s
(3hHYO, aEfj oOaYJ Edi eWGdYI cJGH KeGQ GdbdhH aj GdeVGa hGdefShH CHj efUhQ GdKYGdHj s
(3BNQgG (B:s
(3bdJ(B: (3bO CWdbJ YfGf Gdbde aj GdJbGW aQGFO gPG GdcJGH, hhajJ MSf GdGNJUGQ hChOYJg aj Vef GdeNJUQ, hfbGhg PG GdeYJUQ s
(3HBNQgG eWGdYg JeJ SfI (B1140(3g```s
(3HgG fXGe GdJYbjHIs
(3hHChdgG agQS dCHhGH GdcJGHs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs